Phenotypic spectrum of patients with mutations in CHD7: clinical implications of endocrinological findings. Issue 2 (11th February 2022) - Kim, Ja Hye; Choi, Yunha; Hwang, Soojin; Kim, Gu-Hwan; Yoo, Han-Wook; Choi, Jin-Ho
Abstract : Objective: Heterozygous CHD7 mutations cause a broad spectrum of clinical phenotypes ranging from typical CHARGE syndrome to self-limited delayed puberty. This study aimed to investigate the clinical characteristics of endocrine dysfunction in patients with CHD7 mutations. Methods: The clinical features and endocrine findings from 30 patients with CHD7 variants were retrospectively reviewed. A diagnosis of CHARGE syndrome was based on the Verloes diagnostic criteria. Results: Seventeen patients fulfilled the criteria for typical CHARGE syndrome, one patient for partial/incomplete CHARGE, and the remaining eleven patients had atypical CHARGE syndrome. One patient was diagnosed with Kallmann syndrome and unilateral deafness. The most frequently observed features were inner ear anomalies (80.0%), intellectual disability (76.7%), and external ear anomalies (73.3%). The mean height and weight SDSs at diagnosis were −2.6 ± 1.3 and −2.2 ± 1.8, respectively. Short stature was apparent in 18 patients (60%), and 1 patient was diagnosed with growth hormone deficiency. Seventeen males showed genital hypoplasia, including micropenis, cryptorchidism, or both. Seven patients after pubertal age had hypogonadotropic hypogonadism with hyposmia/anosmia and olfactory bulb hypoplasia. Truncating CHD7 mutations were the most common ( n   = 22), followed by missense variants ( n   = 3), splice-site variants ( n   = 2), and large deletion ( n   = 2). Conclusions: A diverse phenotypic spectrum was observed in patients with CHD7 variants, and endocrine defects such as short stature and delayed puberty occurred in most patients. Endocrine evaluation, especially for growth and pubertal impairment, should be performed during diagnosis and follow-up to improve the patient's quality of life.